Meningkatkan Keterampilan Motorik Halus Berbantuan Media Kolase Pada Anak Usia Dini - Kadek Hengki Primayana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Education is an important part of life that also distinguishes humans from other living things. While humans learn towards maturity in order to lead a more meaningful life. Children receive education from their parents and when these children are adults and their families will educate their children. Develop fine motor skills of children aged 5-6 years by using collage media in early childhood according to the procedure, which is to plan pictures, prepare tools and materials for use in collage activities, describe and introduce the tools and materials that will be made for collage activities. Keywords: Fine Motor and Collage